Delay in liver bud development during early embryogenesis leads to violation of epicardium formation and its epithelial-to-mesenchymal transformation, but do not affect coronary endothelium formation. - Pototskaya, O. Yu.; Tverdokhleb, I. V. (Морфологія / Morphologia / Morfologìâ, 2010)
Despite intensive investigation of heart embryogenesis the origin of coronary endothelium is still under debate. Existence of close interrelation between proepicardium, liver bud, sinus venosus and early coronary vessels is obvious, but the nature of this interconnection is unclear as well as exact source of endothelial cells. Thus, the purpose of our research was to investigate the effect of inhibition of liver bud development on formation of coronary vessels. To inhibit the liver bud we injected aminoguanidine sulfate into the yolk sack of chick embryos on 14 stage of development by HH (first group) - to prevent contact between proepicardium and liver, and on 16 stage (second group) to allow contact between proepicardium and liver during a short period of time. In the first group it was observed the violation of epicardium formation and early death during first 3 days of incubation. At embryos it was revealed thinning of myocardium and atrio-ventricular cushions, abnormal looping – presumably due to the absence of epicardium. The death was caused by heart insufficiency. In the second group it was observed the beginning of epicardium formation, but the heart defects were the same as in the first group – presumably due to the absence of epicardium-derived cells. At embryos of this group, who survived till 26 stage of development (4.5 day of incubation), despite absence of cellular component in subepicardial space and almost completely absence of liver, we observed formation of coronary vessels. They were concentrated on the dorsal surface of atrio-vetricular channel and were presented by continuation of endothelium of the sinus venosus.